Central European regional cooperation and small states interest-advocacy in the European Union - Ákos, Ákos (POLARITIES, 2024)
Regional cooperation is a traditional tool of small state interest-advocacy as they can amplify the voice of states with individually small influence. There are many regional groups in Central Europe, a region rich in small states, whose stated aim is to enhance cooperation amongst its members at the EU level. This paper analyses the role of five regional groups (Visegrád Group, Slavkov format, Salzburg Forum, Central European Defence Cooperation, Central Five) in the intra-EU diplomatic endeavours of four Central European small states (Austria, Czechia, Hungary, Slovakia) after Russia’s invasion of Ukraine in 2022. The results shows that only the Visegrád Group and the Slavkov format has any meaningful role in the interest-advocacy of the analysed small states in the EU.